The role of dynamic and diffusion weighted magnetic resonance imaging in differentiating malignant and benign portal vein thrombosis - Koç, Mustafa (My University, 2018)
Aim: The aim of this study was to evaluate the role of dynamic and diffusion-weighted (DW) magnetic resonance imaging (MRI) in the differentiation of benign from malignant thrombus in patients diagnosed with portal vein thrombosis.Material and Methods: A total of 56 patients were analyzed, 27 with benign and 29 with malignant thrombus on abdomen dynamic and DW MRI. The b-value of DW MRI was 400 and 1,000 mm2/sec. ADC of portal vein thrombosis was measured. Characteristics ofthe DW MRI signal were recorded. Contrast imaging of the thrombus was performed. The diameter of the portal vein was measured. A comparison of the ADC values between the malignant and benign groups was made using the Mann-Whitney U test.Results: The mean ADC values of benign thrombus were calculated as 1.03±0.27 x 10-3 mm2/sec for b400, and 1.01±0.23 x 10-3 mm2/sec for b1000. The mean ADC values were calculated as 0.93±0.13 x 10-3 mm2/sec for b400 and 0.88±0.26 x 10-3 mm2/ sec for b1000 for malignant thrombus. No statistically significant difference was found between the groups (p=0.778). Malignant thrombus was reported to have higher signal intensity compared to the benign cases in DW MRI. Arterial mild contrasting was found with malignant thrombus with dynamic MRI on subtraction images. Statistically, a significant difference was found between the groups for portal vein diameter (p<0.05).Conclusion: Our results show that the DW MRI signal characteristics and dynamic MRI contrast media enhancement, with measurements of thrombosed portal vein diameters, are helpful in the differential diagnosis.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Patoloji